2007
DOI: 10.1038/sj.onc.1210662
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma invasion in TGFβRII-deficient cells is mediated by CCL5/RANTES

Abstract: Recently, we identified a lung adenocarcinoma signature that segregated tumors into three clades distinguished by histological invasiveness. Among the genes differentially expressed was the type II transforming growth factor-b receptor (TGFbRII), which was lower in adenocarcinoma mixed subtype and solid invasive subtype tumors compared with bronchioloalveolar carcinoma. We used a tumor cell invasion system to identify the chemokine CCL5 (RANTES, regulated on activation, normal T-cell expressed and presumably s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 22 publications
3
55
0
Order By: Relevance
“…CCL5 was previously associated with the progression of breast cancer in several independent studies, but only a direct effect on tumor cells was examined. 29,30,36,46,47 Accordingly, CCL5 derived from mesenchymal stem cells was found to induce a metastatic phenotype through binding to its receptor CCR5 on tumor cells within the primary tumor that increased metastasis to the lungs. 29 In our model we observed a CCL5-dependent recruitment of monocytes to metastasizing tumor cells, suggesting a function of CCL5 in shaping the metastatic microenvironment rather than directly affecting tumor cells (supplemental Figure 11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCL5 was previously associated with the progression of breast cancer in several independent studies, but only a direct effect on tumor cells was examined. 29,30,36,46,47 Accordingly, CCL5 derived from mesenchymal stem cells was found to induce a metastatic phenotype through binding to its receptor CCR5 on tumor cells within the primary tumor that increased metastasis to the lungs. 29 In our model we observed a CCL5-dependent recruitment of monocytes to metastasizing tumor cells, suggesting a function of CCL5 in shaping the metastatic microenvironment rather than directly affecting tumor cells (supplemental Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…40 Moreover, previous findings showed that CCL5 was detected in pulmonary stromal fibroblasts of human lung adenocarcinoma specimens. 36 Thus, activated interstitial fibroblast could be Mean Ϯ SEM; n ϭ 3. As positive controls, HMVECs were stimulated with TNF␣ (10 ng/mL) and interferon ␥ (1 ng/mL).…”
Section: Ccl5 Is Expressed In the Metastatic Microenvironment And Medmentioning
confidence: 99%
See 1 more Smart Citation
“…KLF13 can play the role of an activator, as it does for CCL5 (RAN-TES) [Song et al, 1999], or that of a repressor, as it does for CYP1A1 [Kaczynski et al, 2003]. This is of particular importance, since CCL5 is a chemotactic chemokine in inflammatory cells and is overexpressed in lung cancer, breast cancer, prostate cancer, melanoma, T-cell leukemia, ovarian cancer, and oral cancer [Negus et al, 1997;Robinson et al, 2003;Mori et al, 2004;Vaday et al, 2006;Karnoub et al, 2007;Borczuk et al, 2008;Chuang et al, 2009], and CYP1A1 plays a role in head and neck and lung cancers [Agundez, 2004;Li et al, 2004;Hiyama et al, 2008]. KLF13 is also required for the expression of cyclin D1, which is a known oncogene in OSCC [Nemer and Horb, 2007].…”
mentioning
confidence: 99%
“…Supporting the last two possibilities, both epidermal and stromal cells showed increased nuclear pSmad2 in Smad4 KO skin ( Figure 6). Moreover, several potential TGF␤ target genes with protumorigenic functions, including CCL5, 19,21,30 CCL20, 22,[31][32][33][34] VEGFA, and MMPs, were elevated in Smad4 KO skin and during wound healing. Some of these molecules (eg, CCL5, CCL20, VEGFA, and MMP14) were further elevated in Smad4 KO SCCs when compared with Smad4 KO wounds, which could be caused by further elevation of TGF␤1 levels or additional oncogenic alterations in Smad4 KO SCCs.…”
Section: Epidermal Smad4 Loss Affects the Stroma In Wound Healing Andmentioning
confidence: 99%